Thematic Interpretation of Student Management in Educational Institutions - Asep Irfan Fanani (Departement of PAI, Universitas Majalengka, 2023)
The process of interpreting the Qur'an by collecting verses that have the same purpose and meaning in discussing a theme, arranging them according to the time it is derived by examining the causes of their derivation, and then providing explanations, descriptions, comments, and the main content of the sentence is the meaning of